HUBUNGAN PERSEPSI PESERTA DIDIK BINTARA TERHADAP KOMPETENSI PEDAGOGIK PENDIDIK DENGAN MOTIVASI BELAJAR PESERTA DIDIK BINTARA DI SEKOLAH POLISI NEGARA CISARUA BANDUNG - Rizal Maulana Muhammad, - (2018)
Bandung State Police School Cisarua is a place of education and training especially for new members which performed for seven months. Taking into account the intensity of the duration of education and training for Police Bintara candidates which were relatively short certainly requires a synergistic effort between the elements of educators and students. Pedagogical competence becomes an important instrument to increase the motivation of students to be educated so that the success of teaching and learning process can be achieved. This study aimed to determine (1) students' perceptions of the pedagogical competence of educators (2) students' motivation (3) the relationship of students' perceptions to pedagogical competence of educators with learning motivation of the students. The method used descriptive correlational research method. The total population were 676 students of Public Order Task Force with the number of samples were 87 students of Public Order Task Force. The data were collected by questionnaires. They were analyzed by using Rank Spearman correlation coefficient test. Based on the results of the calculation of the correlation coefficient pedagogic competence educators had a strong relationship with the students' learning motivation. The result of hypothesis test proved that there was a significant correlation between students' perception toward pedagogic competence of educator with motivation of the comissioned students with contribution as much as 42,1%. ---Sekolah Polisi Negara Cisarua Bandung merupakan tempat pendidikan dan pelatihan khususnya untuk anggota baru yang dilakukan selama tujuh bulan. Memperhatikan intensitas lamanya waktu pendidikan dan pelatihan bagi calon Bintara Polri yang relatif singkat tentunya membutuhkan upaya yang sinergis antara unsur tenaga pendidik dan peserta didik. Kompetensi pedagogik menjadi instrumen penting untuk meningkatkan motivasi belajar peserta dididik agar keberhasilan proses belajar mengajar dapat tercapai. Penelitian ini bertujuan untuk mengetahui (1) presepsi peserta didik terhadap kompetensi pedagogik pendidik (2) motivasi belajar peserta didik (3) hubungan persepsi peserta didik terhadap kompetensi pedagogik pendidik dengan motivasi belajar peserta didik. Metode yang digunakan yaitu metode penelitian deskriptif korelasional. Jumlah populasi sebanyak 676 peserta didik Bintara Tugas Umum dengan jumlah sampel 87 peserta didik Bintara Tugas Umum. Pengumpulan data menggunakan angket. Analisis data dilakukan dengan menggunakan uji koefisien korelasi Rank Spearman. Berdasarkan hasil perhitungan koefisien korelasi kompetensi pedagogik pendidik memiliki hubungan yang Kuat dengan motivasi belajar peserta didik Bintara Polri. Hasil uji hipotesis membuktikan bahwa terdapat hubungan yang signifikan antara persepsi peserta didik terhadap kompetensi pedagogik pendidik dengan motivasi belajar peserta didik Bintara Polri dengan kontribusi sebesar 42,1%.